Genotype-phenotype correlation in 667 Chinese families with spinocerebellar ataxia type 3. (September 2020) - Du, Yi-Chu; Dong, Yi; Cheng, Hao-Ling; Li, Quan-Fu; Yang, Lu; Shao, Ya-Ru; Ma, Yin; Ni, Wang; Gan, Shi-Rui; Wu, Zhi-Ying
Abstract: Introduction: Due to diverse symptoms of spinocerebellar ataxia type 3 (SCA3) and the high prevalence of SCA3 in China, a more in-depth study of Chinese SCA3 patients in a large cohort is well merited. Methods: During the last 10 years, 730 patients and 133 premanifest individuals from 667 SCA3 families genetically confirmed to have SCA3 were enrolled from three leading academic hospitals in China. The clinical profile and genotype-phenotype correlation were analyzed. Results: A quadratic equation best explained the relationship between the logarithmically transformed age at onset (AAO) and expanded CAG repeats (expCAGs) (r 2  = 0.634, p  < 0.001). The expCAG and AAO in Asian populations and western populations were compared with the Chinese population. SCA3 individuals had shorter normal CAG repeats (norCAGs) than healthy controls (Mann-Whitney, p  < 0.0001). Most (92.1%) SCA3 patients had gait-ataxia onset. Their AAO and expCAGs were not significantly different from SCA3 patients with non-gait-ataxia onset. Limb ataxia and pyramidal impairment occurred less in patients with disease duration >10 years. Intriguingly, onset after parturition happened in 10 female patients with the AAO of 26.7 ± 4.3 years and the expCAG of 77.4 ± 1.4 repeats. Five out of 12 patients with subtype V and larger expCAGs (78.8 ± 4.8 repeats) suffered from spastic gait initially, and 10 out of 12 showed no limb ataxia. Nystagmus happened most frequently (10.5%) in premanifest individuals. Conclusion: We demonstrated the genotype-phenotype correlation in the largest cohort of SCA3 individuals to date, and interestingly found some new phenomena in Chinese SCA3 individuals. Highlights: Heterogenous symptoms were analyzed in 667 Chinese SCA3 families and 92.1% of SCA3 patients initially had gait ataxia. The expCAG and AAO in Asian populations and western populations were compared with the Chinese population. New phenomena including female patients with onset after parturition and the smaller norCAG in SCA3 patients were found.